Polyhexamethyleneguanidine Phosphate-Induced Cytotoxicity in Liver Cells Is Alleviated by Tauroursodeoxycholic Acid (TUDCA) via a Reduction in Endoplasmic Reticulum Stress - Sou Hyun Kim; Doyoung Kwon; Seunghyun Lee; Sung Hwan Ki; Hye Gwang Jeong; Jin Tae Hong; Yun-Hee Lee; Young-Suk Jung (Cells, 2019)
Polyhexamethyleneguanidine phosphate (PHMG-P) is a widely used polymeric antimicrobial agent known to induce significant pulmonary toxicity. Several studies have reported that the liver also can be a target organ of polyhexamethyleneguanidine (PHMG) toxicity, but the exact effect of this compound on liver cells is not well understood. To identify the mechanism of PHMG hepatotoxicity, HepG2 cells were exposed to PHMG-P for 72 h. The cell viability was significantly decreased by PHMG-P in a time- and concentration-dependent manner. The mitochondrial membrane potential was markedly reduced by PHMG-P and the apoptotic signaling cascade was activated. The increases observed in C/EBP homologous protein (CHOP), p-IRE, and p-JNK levels in PHMG-P-treated cells indicated the induction of endoplasmic reticulum stress. To verify the role of ER stress in PHMG-P-induced cytotoxicity, HepG2 cells were pretreated with the chemical chaperone, tauroursodeoxycholic acid (TUDCA) and then co-treated with TUDCA and PHMG-P for 24 h. Interestingly, TUDCA inhibited PHMG-P-induced ER stress and cytotoxicity in a dose-dependent manner. The apoptotic cell death and mitochondrial depolarization were also prevented by TUDCA. The proteins involved in the apoptotic pathway were all normalized to their control levels in TUDCA-treated cells. In conclusion, the results suggest that PHMG-P induced significant cytotoxicity in liver cells and ER stress-mediated apoptosis, which may be an important mechanism mediating this hepatotoxicity.